2008
DOI: 10.1111/j.1525-1470.2008.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Microphthalmia with Linear Skin Defects: A Case Report and Review

Abstract: Microphthalmia with linear skin defects syndrome is an X-linked dominant disorder characterized by microphthalmia and other ocular anomalies as well as linear, jagged skin defects typically involving the scalp, face, neck, and upper trunk. Other associated characteristics include short stature, developmental delay, congenital heart defects, diaphragmatic hernia, agenesis of the corpus callosum, anencephaly, hydrocephalus, and seizures. Microphthalmia with linear skin defects syndrome is now known to be associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
(77 reference statements)
0
22
0
Order By: Relevance
“…MLS is an X-linked dominant, male lethal phenotype characterized by microphthalmia or other ocular features, including corneal opacities in approximately 35 % and lesions of the skin that heal with age. MLS has also been associated with other variable systemic defects including short stature, congenital heart disease, central nervous system defects including developmental delay, genitourinary anomalies and hearing defects (Sharma et al 2008). The HCCS gene has 7 exons with exons 2–7 encoding for the protein holocytochrome c synthase (HCCS).…”
Section: Resultsmentioning
confidence: 99%
“…MLS is an X-linked dominant, male lethal phenotype characterized by microphthalmia or other ocular features, including corneal opacities in approximately 35 % and lesions of the skin that heal with age. MLS has also been associated with other variable systemic defects including short stature, congenital heart disease, central nervous system defects including developmental delay, genitourinary anomalies and hearing defects (Sharma et al 2008). The HCCS gene has 7 exons with exons 2–7 encoding for the protein holocytochrome c synthase (HCCS).…”
Section: Resultsmentioning
confidence: 99%
“…3 The combination of microphthalmia with CDH has also been reported because of deletions or variants in other genes or genomic loci. [4][5][6] Here, we investigated a familial case of syndromic microphthalmia in association with CDH, spina bifida and cardiac anomalies. To identify the cause, we performed exome sequencing on two affected male siblings and both parents, which identified a variant in the X-linked PORCN gene as the underlying cause.…”
Section: Introductionmentioning
confidence: 99%
“…Although HCCS is ubiquitously expressed (Schaefer et al, 1996; Schwarz & Cox, 2002), the highly specific clinical features observed in MLS affected females suggest a critical function and a sensitive dosage for HCCS in the eye and the skin. Microcephaly, mental retardation, diaphragmatic hernia and congenital heart defects are additional features less frequently observed in female patients (Morleo & Franco, 2009 [update 2011]; Sharma et al, 2008), implying that non‐random X chromosome inactivation may also influence the MLS phenotype (Franco & Ballabio, 2006; Morleo & Franco, 2008; Van den Veyver, 2001).…”
Section: Introductionmentioning
confidence: 99%